The Impact of Training on Teamwork and Simulated Debriefings on Real-Life Cardiopulmonary Arrest Events. (October 2021) - Hunt, Tara Mahramus; Anderson, Mindi; Vo, Mai; Penoyer, Daleen Aragon
Background: Prior to the study, debriefings post-real-lifecardiopulmonary arrest at the associated hospital were conducted only 3% of the time. However, debriefings post-cardiopulmonary arrests are recommended by multiple entities to improve team performance. Methods: A course onteamwork, education on a structured method ofdebriefing, anddebriefing practice via simulated role-play were provided to resuscitation team members. A prospective, mixed methods study including team member perceptions ofdebriefings and the number ofdebriefings conducted post-cardiopulmonary arrests were measured after the intervention. Results: Debriefings increased from 3% to 39%.Debriefings were valued by all team members. Themes generated from team members' comments included improvement, communication, and team function. Conclusions: Debriefings post-real-lifecardiopulmonary arrest events are feasible in a hospital setting.Teamwork principlestraining with simulated role-play ofdebriefing can impact the process of whetherdebriefings occur and are highly regarded by multidisciplinary team members.